Cohort fertility a case study of a Philippine community - Abeleda, Amparo Mariano 1941- (Quezon City Population Institute, University of the Philippines Diliman, 1970)
Changes in marriage and childbearing patterns can cause wide fluctuations in annual birth rates despite a constant average family size. One way to unfold these influences from one another is through an explicit longitudinal approach. Cohort analysis is such method. The present paper is an application of this method of study aimed at investigating changes in fertility trends in terms of timing patterns of successive generations of women differentiated according to their year of birth, age at marriage, education, work experience and annual family income.

This study utilized pregnancy histories of 1,232 married women interviewed during a fertility survey conducted in Imus, Cavite, in the early part of 1967. Information derived from the pregnancy histories was transformed into conventional fertility rates following a method described by Bogue. The fertility rates derived from this procedure ideally conform to age-specific birth rates based on complete birth registration.

Parity progression ratios and actual birth intervals in months are other fertility measures employed in this study to determine intercohort trend in birth timing. The trio of socio-economic indicators mentioned above was controlled in order to determine if it had any bearing on the observed course of fertility in recent years.
Thesis
Keywords: Ferility, Human; Philippines -- Population